The pharmacotherapy of low back pain - Oppel BW Greeff (South African Family Practice, 2018)
About 60–80% of patients visiting a physician have at some stage in their lives suffered from low back pain. The annual incidence in adults aged 35–55 years in developed countries is up to 45%.1 The differential diagnosis is broad and includes muscular strain, primary spine disease like disc herniation or degenerative arthritis, systemic diseases like metastatic cancer and regional diseases like aortic aneurisms. In the majority of cases, a specific diagnosis cannot be made. Most patients will improve in 1–4 weeks and will only need treatment for the acute symptoms after the initial history and physical examination. If, however, the pain recurs or worsens, the patient must be thoroughly examined and a specific diagnosis can become a challenge.